Implementasi Sistem Pakar Metode Forward Chaining dan Certainty Factor pada Ayam Pedaging - Asep Afandi; Dwi Marisa Efendi (Prosiding SISFOTEK, 2020)
Disease attacks the farming, it will reduce the poultry productivity. When the chicken get sick, doctors are expected to be able to help treat and prevent diseases to avoid becoming epidemic. However, this does not really help because it takes a long time to call a doctor while the disease keeps spreading. This study aims to build an expert system by applying the Forward Chaining method that has an accuracy calculation to identify broiler diseases and provide a way to overcome it. Expert system development is carried out using the waterfall system development method with the software life cycle approach sequentially including the analysis, design, programming, and testing. The authors used data from PT. Ciomas Adisatwa, a branch of Bandar jaya - Lampung Tengah. The data were directly obtained from Field Extension Officers, through interviews and direct observation. Accuracy measurements were performed using the Certainty Factor methods. Expert System Identification of Broiler Diseases was tested using the Equivalence Class Partitioning method which is a part of Black Box Testing. The tests show Broiler Disease Identification System went well. The Certainty Factor method shows an accuracy of at least 96% for all types of diseases.